PENGEMBANGAN VIDEO ANIMASI SEBAGAI MEDIA EDUKASI ADAB BERSOSIAL MEDIA PADA MATA PELAJARAN PENDIDIKAN PANCASILA PADA KELAS IV SDN 172 INPRES LIMAPOCCOE - Andi Tenri Ulang; Ahmad Syawaluddin; Bhakti Prima Findiga Hermuttaqien (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to produce animated videos as educational media on social media etiquette in the Pancasila education subject for fourth-grade students at SDN 172 Inpres Limapoccoe. The research method used in this study is Research and Development (R&D). The development model used by the researcher was the ADDIE model. The population in this study consisted of 27 fourth-grade students at SDN 172 Inpres Limapoccoe. The results of this study showed that the validation results obtained by subject matter experts were 75% (good), while the validation results obtained by media experts were also 75% (good). After conducting validation with experts, a teacher response test was carried out with a percentage of 82% (very good), a student response test with a percentage of 76% - 93% (very good), and a small group trial was conducted with 6 students. Thus, the research on the development of animated videos as a medium for educating social media etiquette is categorized as very good.